Chapter Ancora sulla fortuna de La Fuerza lastimosa nell'opera del Seicento: Alfonso I di Matteo Noris (Venezia Napoli Palermo) - TEDESCO, Anna (Studi e saggi, 2020)
Lope de Vega's play, La fuerza lastimosa, written around 1599 and first published in 1609, was very popular in Seventeenth-Century Italy, as research by Fausta Antonucci and Salomé Vuelta has demonstrated. Several Italian adaptations are already known, among which a dramma per musica, La forza compassionevole,written by Antonio Salvi and staged in Leghorn in 1694. In the same year, another opera based on Lope's drama was staged in Venice (as Alfonso I) and in Naples (under the title Alfonso il Sesto re di Castiglia). Two years later, this last version was revived in Palermo, again, as in Naples, to celebrate the birthday of King Charles II of Spain. None of these three librettos indicates Lope's authorship nor it has been hypothesized until now. However, the plot of all librettos is clearly based on Lope's play. This chapter aims at illustrating the relation between the librettos for these three performances and La fuerza lastimosa. It also discusses the context of all the stagings and identifies some of the existing musical sources. Finally, it argues that Alessandro Scarlatti could be the author of the Neapolitan score.